Anatomy of Credit-Less Recoveries - Corrado, Luis (World Bank, Washington, DC, 2018)
The recovery from the global crisis that erupted in 2007 shows that the decoupling between real and financial variables during the business cycle can lead to negative and long-lasting consequences for the economy. A key feature of the past global crisis in many countries is that the recovery in aggregate output has not been accompanied by a contemporary pick-up in lending flows to the private sector, rendering the recovery credit-less. This paper uses data on output and credit to study the relative roles of demand and supply drivers of credit growth during economic recoveries on a sample of advanced and emerging countries between 1980 and 2014. Using a simple endowment economy model, the paper shows that credit-less recoveries are correlated with liquidity shocks in real and financial markets and with the pace of private sector deleveraging. The empirical analysis shows that during these episodes demand-side frictions played a relatively larger role in predicting the occurrence of the episodes, reflecting weak demand for liquidity by the private sector in the aftermath of the crisis.